Evaluación sanitaria y productiva de 150 genótipos de cacao (thebroma cacaoL.) en la finca experiemental "La Represa". - Zambrano Montúfar, José Fernando (2012)
As a contribution to improving the national cocoa in terms of health and production, a process of research at the Experimental Farm "Dam" located on the road Quevedo - San Carlos, province of Los Ríos, 150 genotypes of the National Cocoa which were previously selected at the Experimental Farm "La Buseta" located in the parish Tenguel, Canton Guayaquil, Guayas Province for their health and productive characteristics. The genotypes were evaluated phenological and physiologically through an arbitrary scale, the variables evaluated were: budding, flowering, fruiting and Cherelle wilt in the rainy season and dry in the healthcare variables were assessed: number of diseased pods during the rainy season and dry number of witches' broom in July, while in production variables were evaluated variables: length and diameter of the ear, back and groove thickness, index, seed index, cob, number of ears healthy, fresh weight and performance in rainy and dry. After this assessment the full results were driven by 94 genotypes corresponding to 62.66% of which were applied the method comprising descriptive statistics: mean, standard deviation, coefficient of variation, minimum and maximum values, for selection of the best genotypes multivariate analysis was applied comprising: correlation analysis, cluster analysis (clusters) and principal component analysis. The correlation between genotypes and found positive and highly significant correlations for the following variables: total number of diseased pods / number of diseased pods during the dry season (r = 0.99 **), ear diameter / length cob (r = 0.72 **), loin thickness / groove thickness (r = 0.72 **), total yield / number of healthy ears in the dry season, total healthy ears and performance in the dry season ( r = 0.93 **, 0.94 ** and 0.95 **). Following statistical analysis, five genotypes (UICYT-C186, C217-UICYT, UICYT-C119, C114 and UICYT-UICYT-C107) noted for its similarity to the low number of diseased pods and witches' broom, the high number of ears sound and performance in rainy and dry.